Fourteen new species of scuttle flies (Diptera, Phoridae) from Denmark - Disney, R. Henry L; Bøggild, Esben (Zootaxa, 2019)
Megaselia anniduedahlae sp. n., M. balfourbrownei sp. n., M. birgittemarkae sp. n., M. carlkahleri sp. n., M. gerdakahlerae sp. n., M. helleorumae sp. n., M. jonasseni sp. n., M. legrandi sp. n., M. loneviolaae n sp. n., M. parhirticrus sp. n., M. pederseni sp. n., M. thomseni sp. n., Triphleba ehmseni sp. n., and T. papei sp. n., are described from Denmark.